ANALISIS TREND PENCARIAN INFORMASI PERUBAHAN IKLIM DI INDONESIA - Gunawibawa, Eka Yuda; Fardiyan, Ahmad Rudy; Pratama, Prayoga Ardhi (Gapenas Publisher, 2024)
This study identifies groups of active audiences in Indonesia who search for information using the Google Search Engine. Additionally, the research explores the motives of these audience groups based on their search queries. A descriptive quantitative approach was employed, utilizing Google Trends for data collection. The findings indicate the existence of 25 active audiences related to climate change information searches, with these searches distributed across nearly all regions of Indonesia. The identified audience groups predominantly fall into the cognitive category, seeking information, knowledge, and understanding. This is demonstrated by the greater popularity of the term